Intending, acting, and doing. (31st August 2017) - Ferrero, Luca
Abstract : I argue that intending and acting belong to the same genus: intending is a kind of doing continuous in structure with intentional acting. Future-directed intending is not a truly separate phenomenon from either the intending in action or the acting itself. Ultimately, all intentions are in action, or better still, in extended courses of action. I show how the intuitive distinction between intending and acting is based on modeling the two phenomena on the extreme and limiting cases of an otherwise continuous spectrum of the ways in which agents exercise rational active intelligent guidance in the pursuit of goals. I argue that diachronic intentional agency is better understood in terms of continuity and unity of courses of active and intelligent guidance, and that the distinction between intending to do something and doing it is only a derivative and context-dependent segmentation of these continuous courses of rational active intelligent guidance.